Effect of taxonomy and feeding guilds on waterbirds of the Southern Caspian Sea, Iran - Mohammad Hosein Sinkakarimi; Mehdi Hassanpour (PLoS ONE, 2026)
This study measured the concentrations of arsenic (As), cadmium (Cd), chromium (Cr), iron (Fe), manganese (Mn), nickel (Ni), lead (Pb), and zinc (Zn) in the secondary flight feathers of waterbirds wintering along the southern Caspian Sea coast of Iran, in February 2013. Target species included Anas acuta , Anas platyrhynchos , Anser anser , Aythya ferina , Ciconia ciconia , Cygnus olor , Hydroprogne caspia , Mareca penelope , Mergus merganser , Phalacrocorax carbo , and Tringa totanus . Element concentrations ranged from highest in P. carbo (Pb 5.65, Cd 3.29, Cr 5.90, Ni 6.57, As 0.60, Mn 9.30, Zn 147.67, Fe 267.29 µg/g dw) to lowest in M. penelope (As 0.13), C. olor (Cd 0.78, Cr 2.32, Ni 1.22), T. totanus (Fe 115.13), C. ciconia (Mn 4.43), A. anser (Pb 1.24), and A. acuta (Zn 37.40). Element levels varied by feeding guild and avian family: piscivores showed the highest Pb, Cd, Cr, Ni, As and Zn, whereas invertebrate predators had the lowest Cd, As, Zn, Fe. Phalacrocoracidae exhibited the highest overall levels, while Scolopacidae (As, Cd, Fe, Zn), Anatidae (Pb, Ni), and Ciconiidae (Cr, Mn) showed the lowest. Cadmium exceeded 2 µg/g in six species; Cr exceeded 2.8 µg/g in all but A. anser , C. ciconia and C. olor ; Pb exceeded 4 µg/g in P. carbo , with marginal exceedances in four others. Findings indicate elevated trace metal burdens in wintering waterbirds, suggesting ecological risks associated with trophic exposure and habitat contamination.